Konsolidasi demokrasi Indonesia: Tantangan, regresi, dan prospek pasca pemilu 2024 - Putri, Siti Nurfebriyanti (Maliki Interdisciplinary Journal, 2026)
The journey of Indonesian democracy post-1998 Reformation is currently at a critical juncture, marked by democratic regression leading up to and following the 2024 General Election. This study aims to analyze the dynamics of democratic consolidation, identify factors driving the decline in democratic quality, and formulate policy recommendations for its reinforcement. Using a qualitative literature review method, the research finds that while Indonesia has successfully held regular elections, the substantial quality of its democracy has significantly diminished. Key factors driving this regression include the weakening independence of crucial institutions such as the Corruption Eradication Commission (KPK) and the Constitutional Court (MK), particularly regarding Ruling No. 90/PUU-XXI/2023 which sparked concerns over dynastic politics. Furthermore, the dominance of oligarchs, widespread money politics (clientelism), identity politics-based polarization, and the proliferation of digital disinformation have further deteriorated the national political landscape. The 2024 Election, initially expected to be a milestone for democratic maturity, was instead overshadowed by controversies regarding legitimacy and state apparatus neutrality. Nevertheless, optimism remains through the existence of a critical civil society and the active participation of the younger generation. This study recommends comprehensive political party reform, strengthening the system of checks and balances, and enhancing digital and political literacy to ensure the sustainability of inclusive and substantive democracy in Indonesia.